The Backstagers and the ghost light - Mientus, Andy (Mientus, Andy. Backstagers, 2020)
When Jory transfers to St. Genesius Prep, he joins the stage crew and discovers the magic that happens backstage, but when some cast members play with a spirit board, the ghost light goes out and strange things begin to happen.